11.15 MS incidence rates vary threefold by health board in scotland, persistently. Issue 12 (14th November 2019) - Kearns, Patrick; Connick, Peter; Paton, Martin; O'Neill, Martin; O'Riordan, Jonathon; McDonald, James; Colville, Shuna; Ascherio, Alberto; MacDougall, Niall; Chandran, Siddharthan
Abstract : Fifteen regional studies of multiple sclerosis rates have been published in Scotland; spanning some six decades and surveying prevalence, mortality and hospital admissions. However, only one national study has attempted to compare regional rates (using admissions data). We used the Scottish Multiple Sclerosis Register to investigate incidence rates (IR). We present crude and age-adjusted IRs, cumulative incidences, and the sex ratio of cases and rates, for all regions of Scotland: 01/01/2010 to 31/12/2017. The overall IR for Scotland was 8.76/100, 000 person-years (standardized: 8.54), which is high, but likely a conservative estimate of the total burden, including only definite cases. The female-male ratio was 2.3. Regional rates and sex ratios varied significantly – up to threefold – between Health Boards (p<10–13), well correlated with the 1997–2009 admissions data (r=0.85, p<0.001). Significant variation was observed on the mainland, not just on the islands. Lifetime risk ranged from 19.9/1000 for females in Orkney to 1.6/1000 for males in the Borders. This study is the first attempt to analyse the patterns of incidence for the whole of Scotland from prospectively collected data and benefits from a high level of completeness and ascertainment. The wide variation in incidence rates and sex-ratios is unexplained.